Synthesis and Molecular Docking Assay of 2-(3-3,4-dimethoxyphenyl)-6-oxopyridazin-1(6H)-yl)acetohydrazide as a candidate for breast anticancer - Zulmy, Winda Permata; Hendra, Rudi; Shalihah, Putri Mar Atus; Jasril, Jasril (LPPM Universitas Muhammadiyah Riau, 2025)
Pyridazinones are a class of heterocyclic compounds with broad biological activities, one of which is as an anticancer. This study synthesized N-acetohydrazide substituted pyridazinone derivatives and evaluated their potential as breast cancer therapy through molecular docking studies. The target compound, 2-(3-(3-methoxyphenyl)-6-oxopyridazine-1(6H)-yl)acetohydrazide(3), was synthesized through three reaction steps: condensation to form the pyridqzinone core, functionalization of ethyl chloroacetate at the nitrogen position, and substitution of the ethoxy group with hydrazine hydrate. The yield obtained was 48.14%. The purity of the synthesized compound was confirmed through melting point determination and high-performance liquid chromatohraphy (HPLC) analysis, which showed a single dominant peak. Structural elucidation using Fourier-transform infrared (FTIR), mass spectrometry (MS), proton nuclear magnetic resonance (1H-NMR), and carbon-13 nuclear magnetic resonance (13C-NMR) verified the expected structure. Molecular tethering studies against tyrosine kinase (PDB ID: 3ERT) showed that compound (3) has a binding free energy of -7.93 kcal/mol, with two hydrogen bonds formed with residues Glu353 and Leu387. These results indicate that compound (3) has not shown better inhibitory activity than tamoxifen. Nonetheless, this compound fulfils good physicochemical characteristics based on Lipinski's rule, so it remains promising for further development.